Musashi mediates translational repression of the Drosophila hypoxia inducible factor. - Bertolin, Agustina Paola (2016)
Adaptation to hypoxia depends on a conserved α/β heterodimeric transcription factor called Hypoxia Inducible Factor (HIF), whose α-subunit is regulated by oxygen through different concurrent mechanisms. In this study, we have identified the RNA binding protein dMusashi, as a negative regulator of the fly HIF homologue Sima. Genetic interaction assays suggested that dMusashi participates of the HIF pathway, and molecular studies carried out in Drosophila cell cultures showed that dMusashi recognizes a Musashi Binding Element in the 3' UTR of the HIFα transcript, thereby mediating its translational repression in normoxia. In hypoxic conditions dMusashi is downregulated, lifting HIFα repression and contributing to trigger HIF-dependent gene expression. Analysis performed in mouse brains revealed that murine Msi1 protein physically interacts with HIF-1α transcript, suggesting that the regulation of HIF by Msi might be conserved in mammalian systems. Thus, Musashi is a novel regulator of HIF that inhibits responses to hypoxia specifically when oxygen is available.